Effects of mercerization in the chemical and morphological properties of amazon piassava - Rebelo,Viviane (2019)
Abstract The objective of this work was to investigate the effects of mercerization on chemical, morphological and thermal properties of Amazon Piassava Fibers. The effect of this treatment was studied using XRF, SEM, XRD and TGA. The fibers have been treated in 5% and 10% NaOH for 60 min. The XRF results for treated and untreated fibers showed that there is a decrease in the amount of SiO 2 by increasing the NaOH concentration. It has been possible to observe through SEM in untreated fiber that the surface presents a well arranged pattern of silicon rich star-like protrusions. For the two concentrations, SEM allowed to notice that the removal of deleterious surface impurities and fiber roughness was enhanced. The removal of organic material after treatment can be observed in the TGA analysis. XRD analysis indicate an increase in the crystallinity index, 0.19 to 0.31 after the treatment for 10% concentration solutions.